2023
DOI: 10.1371/journal.pone.0282125
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare seeking patterns for TB symptoms: Findings from the first national TB prevalence survey of South Africa, 2017–2019

Abstract: Background Although tuberculosis (TB) symptoms have limited sensitivity they remain an important entry point into the TB care cascade. Objectives To investigate self-reported healthcare seeking for TB symptoms in participants in a community-based survey. Methods We compared reasons for not seeking care in participants reporting ≥1 of four TB screening symptoms (cough, weight loss, night sweats, fever) in the first South African national TB prevalence survey (2017–2019). We used logistic regression analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…South Africa bears a heavy and unsustainable burden of both TB and HIV individually, and nearly 60% of individuals with TB are also living with HIV (South African National Department of Health, 2021). It is further estimated that one-in-five people living with HIV (PLWH) have a comorbid mental disorder (Myer et al, 2008;Zuma et al, 2022) and approximately one-in-three individuals with TBwith or without HIV coinfection -experience severe psychological distress (Peltzer et al, 2012(Peltzer et al, , 2013Walt and Moyo, 2018;Janse Van Rensburg et al, 2020). The high rates of mental disorders and infectious diseases, particularly HIV and TB, highlight the need for task-sharing mental health services and validated screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…South Africa bears a heavy and unsustainable burden of both TB and HIV individually, and nearly 60% of individuals with TB are also living with HIV (South African National Department of Health, 2021). It is further estimated that one-in-five people living with HIV (PLWH) have a comorbid mental disorder (Myer et al, 2008;Zuma et al, 2022) and approximately one-in-three individuals with TBwith or without HIV coinfection -experience severe psychological distress (Peltzer et al, 2012(Peltzer et al, , 2013Walt and Moyo, 2018;Janse Van Rensburg et al, 2020). The high rates of mental disorders and infectious diseases, particularly HIV and TB, highlight the need for task-sharing mental health services and validated screening tools.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis the 2013–2014 Zambian National TB prevalence survey data showed that about 40.5% with bacteriologically confirmed TB were asymptomatic for cough ≥2 weeks [ 28 ]. In a cross-sectional survey in South Africa between 2017–2019, 57.5% of bacteriologically confirmed TB occurred in those who were asymptomatic but had chest Xray abnormalities [ 29 ].…”
Section: Discussionmentioning
confidence: 99%